Sex-specific characteristics of the trunk muscle behaviors in an asymptomatic adult cohort - Fumin Pan; Jingbo Cheng; Chao Kong; Wei Wang; Shibao Lu (European Journal of Medical Research)
Abstract Objectives The trunk muscles play an important role in generating motion and maintaining posture stability. We aimed to investigate the sex-dependent differences in the three-dimensional isometric and isokinetic trunk muscle strength. Methods We included 122 asymptomatic participants (61 males and 61 females) aged from 20 to 35 years and used the BioniX Sim3 Pro device to measure the three-dimensional isometric and isokinetic trunk muscle strength. Results Males displayed greater absolute isometric trunk torques than females (P < 0.05), which vanished after normalized to body weight (P > 0.05). The isometric torque was greatest during extension, then during flexion, lateral bending came next and axial rotation came least (P < 0.05). During isokinetic movements at 15°/s, males in contrast displayed lower trunk torques than females in each direction, both before and after normalized to body weight (P < 0.05). The isokinetic trunk torque decreased with an increasing velocity from 15°/s to 45°/s (P < 0.05), which showed no significant difference between 45°/s and 75°/s (P > 0.05). The isokinetic trunk torque was greatest during extension, then during flexion, lateral bending and then during axial rotation when moving at 15°/s (P < 0.05), and this sequence changed during movements at 45°/s and 75°/s. Conclusions We created a database concerning the isometric and isokinetic trunk torques in an asymptomatic adult cohort. The results could be provided as physiological references in the future for comparison between subjects with and without trunk muscle impairments.